PENGEMBANGAN DESA MANDIRI ADMINISTRASI, PARIWISATA, DAN SENI MENUJU KALIMANTAN TIMUR SEBAGAI IBU KOTA NEGARA BARU DI DESA BUDAYA LEKAQ KIDAU : The Development of Independent Villages for Administration, Tourism, and the Arts Towards East Kalimantan as the New Country's Capital in the Cultural Village of Lekaq Kidau - Nugroho, Bayu Aji; Surya, Satyawati; Gunawan, Asril; Anggriyani, Dian; Musthofa, Dwi; Tekwan, Yuvenalis (Program Studi Sastra Indonesia Universitas Mulawarman, 2022)
Abstract: Cultural and tourism village development is one important aspect that should be prioritized by the government to prepare East Kalimantan as the new capital city of Indonesia. Correspondingly, a series of community service activities in Lekaq Kidau Village, Sebulu District, Kutai Kartanegara, East Kalimantan was carried out to support Lekaq Kidau Village to become an independent village for its administration, arts and culture. This community service activity consists of 6 sessions and 4 materials. The method used is counseling and training techniques related to the introduction of the Faculty of Cultural Sciences, writing official letter administration, tourism development and strategy, and training of performance art. The evaluation results from participants’ understanding increase substantially, where before the material the level of understanding was 23.5% and after the material was delivered it became 70.5% or increased by 47%. While the outputs of this community service activity are published in the journal articles and video profiles of Lekaq Kidau Village. Keywords: development; tourism village; cultural village. Abstrak: Pengembangan sebuah desa budaya dan wisata merupakan salah satu aspek yang seharusnya dijadikan prioritas oleh pemerintah dalam rangka mempersiapkan Kalimantan Timur sebagai Ibu Kota Negara Indonesia yang baru. Didasari oleh hal tersebut, rangkaian kegiatan Pengabdian kepada masyarakat di Desa Lekaq Kidau, Kecamatan Sebulu, Kutai Kartanegara, Kalimantan Timur dilaksanakan untuk menunjang Desa Lekaq Kidau menjadi desa mandiri adminstrasi, seni, dan budaya. Kegiatan pengabdian kepada masyarakat ini terdiri dari 6 sesi dan 4 materi. Metode yang digunakan adalah teknik penyuluhan dan pelatihan terkait pengenalan Fakultas Ilmu Budaya, penulisan tata laksana surat dinas, pengembangan dan strategi pariwisata, dan pelatihan performance art. Hasil evaluasi dari peserta menunjukan adanya peningkatan pemahaman, di mana sebelum materi tingkat pemahaman sebesar 23,5% dan setelah disampaikan materi menjadi 70,5% atau meningkat sebesar 47%. Sedangkan luaran dari kegiatan pengabdian kepada masyarakat ini adalah artikel terpublikasi jurnal dan video profil Desa Lekaq Kidau. Kata Kunci: pengembangan; desa wisata; desa budaya.